2018
DOI: 10.3126/ijssm.v5i3.20614
|View full text |Cite
|
Sign up to set email alerts
|

Determination the Level of Knowledge, Attitude, and Practices Regarding Household Waste Disposal among People in Rural Community of Lahore

Abstract: Introduction: Waste disposal is one of the major environmental problems in all over the world. Improper waste disposal causes breeding and may cause infectious diseases like cholera, small pox, and plague, etc. The knowledge of waste disposal is necessary for health of people's. various study reveal that about 90% of people disposal of waste in open places and use the method of land filling, so increase the problems for health of public and the environment. The study has been carried out for the current status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 5 publications
3
20
1
1
Order By: Relevance
“…However, about 39% of people didn't manage household solid waste properly in the world [4]. In India, it was estimated that people of the municipal area generated household solid waste daily at 160,000 MT (Metric Ton) [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, about 39% of people didn't manage household solid waste properly in the world [4]. In India, it was estimated that people of the municipal area generated household solid waste daily at 160,000 MT (Metric Ton) [5].…”
Section: Introductionmentioning
confidence: 99%
“…A prior study revealed that the majority of the people (53%) living in a community in Bangladesh are unaware to manage the household solid waste properly [9]. However, in Pakistan, 28% of the community people are not aware to manage household solid waste [4]. Approximately 41% of community people in Malaysia had inadequate awareness regarding household solid waste management [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampah dinilai sebagai masalah yang tidak pernah tuntas dan menjadi salah satu penyebab kerusakan lingkungan. Sampah merupakan bentuk konsekuensi dari adanya aktivitas manusia yang terus diproduksi dan tidak pernah berhenti selama manusia tetap ada.Volumenya akan bertambah seiring dengan pertambahan penduduk (Ambrin Shahzadi, 2018). Hal ini diperparah dengan kurangnya kesadaran masyarakat dalam membuang dan mengelola sampah, kurangnya jumlah tempat pembuangan akhir sampah (TPA), dan kemampuan pemerintah untuk mendanai tempat pengelolaan sampah masih sangat kurang (Ali Almasi, 2019).…”
Section: Pendahuluanunclassified
“…A clean environment not only promotes good health but also enhance the quality of life. 1 According to WHO (2016) 13 million people die yearly due to environmental issues that can be prevent and it was estimated that 24% disease burden and 23% of total deaths across the world are due to environmental elements. 2 The waste management refers to the steps of process which starts with a collection of waste, segregation of waste, storage of waste, transportation followed by its treatment and at the end its disposal.…”
Section: Introductionmentioning
confidence: 99%